Metatranscriptomic Analysis of the Chicken Gut Resistome Response to In-Feed Antibiotics and Natural Feed Additives - Koorakula, Raju; Schiavinato, Matteo; Ghanbari, Mahdi; Wegl, Gertrude; Grabner, Nikolaus; Koestelbauer, Andreas; Klose, Viviana; Dohm, Juliane C.; Domig, Konrad J. (Frontiers in Microbiology, 2022)
The emergence of resistance against common antibiotics in the gut microbiota is a major issue for both human and livestock health. In poultry farming, antibiotics have been used for decades to promote growth and health. However, despite their importance and the known associated risks, the effect of antibiotics on gut microbiota biodiversity and antibiotic resistance gene expression (i.e., resistome expression) are not fully understood. In this study, we performed shotgun metatranscriptomic sequencing to better understand the dynamics of the resistome in response to different dosages and treatments with an antibiotic or a phytogenic feed additive. Broiler chickens received zinc-bacitracin (either at the growth promoter dosage, i.e., “AGP” or at therapeutic dosage, i.e., “AB”), a phytogenic feed additive (PFA) or combinations of those treatments. Feces were sampled on Days 3, 14, 21 and 35. Over the course of the trial, PFA treatments increased the abundance of Firmicutes such as Lactobacillus and resulted in a lower abundance of potential pathobionts such as Escherichia, while the latter group increased significantly in the feces of chickens that received either AGP or AB doses of bacitracin. Tetracycline resistance and aminoglycoside resistance were the predominant antibiotic resistance gene (ARG) classes found, regardless of the treatment. PFA application resulted in a decrease in ARGs compared to those in the control group and other antibiotic treatment groups. In summary, the findings from this study demonstrate the potential of phytogenic feed additives as an alternative to antibiotics in poultry farming, with the added benefit of counteracting antimicrobial resistance development.